2019
DOI: 10.1002/chem.201900462
|View full text |Cite
|
Sign up to set email alerts
|

Thiadiazolo‐Azaacenes

Abstract: This work reports the synthesis and characterization of bis-and tetrakis(thiadiazolo)-appended di-and tetraazaacenes,d isplaying up to seven catenated benzene/pyrazine rings. The targetsa re obtained by condensation of benzo-bis(thiadiazole)-4,5-dione with aromatic di-and tetraamines. The condensation products-up to a heptacene-like species-are stable but can be insoluble. Soluble derivatives are readily processible,b ut do not show enhanced electrona ffinities, as the two or four attached benzothiadiazole uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The concept is not limited to the introduction of hydrocarbon aprons; thiadiazolo units also stabilize the acene scaffold. 68 Over all, the stability of such materials is much improved but at a cost. In our next series of experiments, we plan to extend this concept to butterfly protected nonacenes to test the limits (of stabilizing power) of this concept.…”
Section: Tetrahedral Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept is not limited to the introduction of hydrocarbon aprons; thiadiazolo units also stabilize the acene scaffold. 68 Over all, the stability of such materials is much improved but at a cost. In our next series of experiments, we plan to extend this concept to butterfly protected nonacenes to test the limits (of stabilizing power) of this concept.…”
Section: Tetrahedral Speciesmentioning
confidence: 99%
“…In our benzo-stabilized species, the two added phenanthrene rings equal one benzene ring electronically. The concept is not limited to the introduction of hydrocarbon aprons; thiadiazolo units also stabilize the acene scaffold . Over all, the stability of such materials is much improved but at a cost.…”
Section: Stabilization Strategies For Tetraazaheptacenes: Butterflies...mentioning
confidence: 99%
“…From 1 + + C to 3 + + C,t he oxidation potentials increase from 0.14 V to 0.26 V, while the reductionp otentials decrease from 0.63 V to 0.34 V. The radical cations become more difficult to oxidize and easier to reduce as ac onsequence of extension of the pconjugated systems. NICS(1) zz calculations [14] were performed to study the aromaticity of the neutralc ompounds and their radicalc ations.T he NICS-values of the inner N,N'-dihydropyrazine (see Figure 2) are positive,w ith their values surpassing + 19.8, indicating local antiaromaticity. [15] This antiaromaticity decreases from 1 to 3, which might be ascribed to the differencei nb ond orders of the fused bond between the dihydropyrazine core and the outer arene groups( benzene, naphthalene andacombination of both).…”
Section: Compmentioning
confidence: 99%
“…Later Bunz et al introduced thiadiazolo-azacene (BDT 4) (Figure 3d) and showed that it had natural tendency to crystalize in association with half mole of solvent (there it was dichloromethane). [51] BDT 4 participates in head-on dimerization through in SÀ N interactions with a d SÀ N of 3.35 Å (Figure 3f). Again Bunz et al introduced spiro-like thiadiazole functionalized azacene (BDT 5) and utilized that as an acceptor for bulk heterojunction (BHJ) solar cells.…”
Section: He Received Phd From Indian Institute Of Science Education A...mentioning
confidence: 99%
“…[46] 74% of total structures studied showed at least one '2SÀ 2N square' interaction (Figure 6). Benzo-tail (Figure 1c [49] (c), thiadiazolo-azacene (BDT 4) and their dimolecular assemblies (d, f); [51] Benzothiadiazole based twisted acenes (BDT 5) and their dimerization through SÀ N interaction (e, g) [52] Table 1. Some SÀ N interaction distance reported in case heteroacenes.…”
Section: He Received Phd From Indian Institute Of Science Education A...mentioning
confidence: 99%